Rules of the Game: An Introduction to the Standards-Related Work of the International Labour Organization - International Labour Organization (International Labour Organization, 2019)
The Rules of the Game: An introduction to the standards-related work of the ILO provides a brief presentation of the ILO’s standards policy with a view to facilitating understanding and ownership by the ILO’s traditional constituents, as well as the United Nations system, non-specialists and the broader public. In its first section, the publication recalls the underlying reasons for and utility of the ILO’s standards-related action at both the national level and in the current context of globalization. The content of international labour standards is then presented thematically in the second section. The third section consists of a description of the supervisory mechanisms of the application of international labour standards by ILO member States. The updating of this reference work, which was first published in 2005 and the most recent edition of which is dated 2014, bears witness to the dynamic nature of the ILO’s standards policy. The new 2019 edition, which coincides with the ILO’s centenary, describes recent developments, including the new instruments adopted, the launch of the Standards Centenary Initiative, which is intended to strengthen the supervisory system, and the establishment of the Standards Review Mechanism. It also places in perspective the essential contribution of international labour standards to the 2030 Sustainable Development Agenda adopted by the Member States of the United Nations in 2015, and the more general reflection on the Future of Work. This edition, prepared by Eric Gravel, of the International Labour Standards Department, contributes to promoting the Organization’s standards-related action and disseminating more broadly information on its standards-related mandate.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; employment / emprego

Managing for Sustainable Development Impact - Kusters, Cecile; Batjes, Karen; Wigboldus, Seerp; Brouwers, Jan; Baguma, Sylvester Dickson (Practical Action Publishing Ltd, 2017)
This guide is about managing development initiatives and organizations towards sustainable development impact. It builds on the work of Guijt and Woodhill in the 2002 IFAD publication Managing for Impact in Rural Development: A Guide for Project M&E. Since then, the managing for sustainable development impact (m4sdi) approach has evolved with insights and feedback from CDI colleagues, clients, partners, and over 800 people who have been trained in its use. In addition, the authors have drawn on the work of many others. m4sdi is an integrated, results-oriented management approach, which can be used across a range of sectors and domains in a variety of contexts, and aims to contribute towards the Sustainable Development Goals (SDGs). It seeks to integrate ideas and practices from a range of approaches and methodologies for planning, monitoring and evaluation, using appropriate methods or tools that engage people in a process of learning and adaptation. It is specifically aimed at strengthening the readiness of leaders, decision-makers and development practitioners to effectively manage their initiatives/organizations in complex settings. m4sdi belongs to a special niche of management approaches, providing relevant perspectives on what makes for effective management for those directly involved in managing initiatives/organizations and wider groups of stakeholders. Many of the people trained in m4sdi have become believers and practitioners of the approach because it addresses several of the most serious concerns in development, such as the difficulty in reaching primary stakeholders, designing effective strategies and related monitoring and evaluation (m&e), focusing on capacity development and change management, and achieving sustainable development impact. The strength of m4sdi lies in its people-centred approach and how it seeks to integrate management processes within a complex environment. The evolvement of the approach needs to be documented to share lessons learned and support capacity development. And so the principles and practices covered in this guide relate to a variety of development initiatives/organizations in the fields of agriculture, food security, local economic development, value chains, enterprise development, and ecosystem governance. Much of the discussion takes place within the often complex context of development. As such, the guide aims to find a good balance between comprehensiveness and the principle of ‘less is more’.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia

Political economy of decentralisation in Mozambique: dynamics, outcomes, challenges - Weimer, Bernhard; Carrilho, João (Instituto de Estudos Sociais e Económicos (IESE), 2017)
The book approaches the topic in a multidisciplinary and multisectoral manner and considers different viewpoints, including political, institutional and that of public administration, finances and society. The authors look at the relationship between decentralisation and democratisation, a subject debated in political sciences: Does decentralisation correspond to a more advanced level of democracy? Regarding its life as a democracy, Moçambique is still a young country and the book provides a clear picture of the history of decentralisation from 1992 to today. Its basic argument is that the political class which has been in power since Independence systematically sought to limit or, on occasion, halt decentralisation. Is this thesis acceptable? And is it sustained by the evidence which the book produces? In general, it is possible to reply affirmatively to both questions. The fact that the government has increased the number of districts, some of which perfectly overlap with the territory of the respective municipalities, is offered as proof to verify the central proposition. Furthermore, in the context of today’s political discourse around the future, the government’s reservation in increasing the number of municipalities constitutes one of countless demonstrations of how cautious the government’s approach to this subject is.
Keywords: *tagged; G - Mozambique / Moçambique; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); decentralization / descentralização; governance / governação; government policy / politica governamental

Gender Dimensions of Investment Climate Reform: A Guide for Policy Makers and Practitioners - Simavi, Sevi; Manuel, Clare; Blackden, Mark C. (The World Bank, 2010)
Promoting women’s economic empowerment is increasingly seen as one of the most important driving forces behind economic growth and the fight against poverty. Women’s economic participation as entrepreneurs, employees, and leaders is recognized as a measure of a country’s dynamism and viability.This main goal of this volume is to provide fresh thinking on how to solve common issues women entrepreneurs and employees face in the investment climate area. It presents actionable, practical, replicable, and scalable tools to promote gender-sensitive investment climate reforms that would equally benefit both women and men. Specifically, the book seeks to enable development practitioners and policy makers who are not gender specialists to diagnose gender issues in an investment climate reform area, design creative and practical solutions and recommendations to address gender constraints, and to oversee the effective monitoring and evaluation of the implementation of those recommendations.This guide highlights the economic rationale for gender inclusion in investment climate reform work and outlines the broader overarching framework within which gender-informed investment climate work can take place. It also provides the monitoring and evaluation framework, with particular emphasis on establishing appropriate baselines to facilitate the measurement of gender-informed changes in the business environment. A step-by-step project management process gives the reader specific guidance on key investment climate areas, namely: (i) business start up and operation, (ii) business taxation, (iii) trade logistics, (iv) special economic zones, (v) alternative dispute resolution, (vi) investment policy and promotion and (vii) secured lending.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; empowerment / empoderamento; entrepreneurship / empreendedorismo; gender / género

The group effect: Social cohesion and health outcomes - Bruhn, John (Springer New York, NY, 2009)
Sociologists and anthropologists have had a long interest in studying the ways in which cultures shaped different patterns of health, disease, and mortality. Social scientists have documented low rates of chronic disease and disability in non-Western societies and have suggested that social stability, cultural homogeneity and social cohesion may play a part in explaining these low rates. On the other hand, in studies of Western societies, social scientists have found that disease and mortality assume different patterns among various ethnic, cultural and social-economic groups. The role of stress, social change and a low degree of cohesion have been suggested, along with other factors as contributing to the variable rates among different social groups. Social cohesion has been implicated in the cause and recovery from both physical and psychological illnesses. Although there has been a large amount of work established the beneficial effects of cohesion on health and well-being, relatively little work has focused on HOW increased social cohesion sustains or improves health. This work is based on the premise that there are risk factors, including social cohesion that regulate health and disease in groups. One of the challenges is how to measure social cohesion - it can be readily observed and experienced but difficult to quantify. A better understanding of how social cohesion works will be valuable to improving group-level interventions. © Springer Science+Business Media, LLC 2009. All rights reserved.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; G - north / norte; L - english / inglês; Northern PEA; health / saúde

State Recognition and Democratization in Sub-Saharan Africa: A New Dawn for Chiefs? - Buur, Lars; Kyed, Helene Maria (Governance, Security and Development, 2007)
State Recognition and Democractization in Sub-Saharan Africaآ explores the link between liberal-style democratization and state recognition of traditional authority in Sub-Saharan Africa. Being critical and empirically grounded, the book explores the complex, often counter-balancing consequences of the involvement of traditional authority in the wave of democratization and liberal-style state-building that has rolled over sub-Saharan Africa in the past decade. It scrutinizes how, in practice, traditional leaders are being drawn into governance in Mozambique, Zambia, Namibia, Malawi, Burkina Faso, and the Somali region of Ethiopia, and relates these developments to state governance in the declining democracy of Zimbabwe and the emerging state of Northern Somalia.
Keywords: G - Mozambique / Moçambique; G - north / norte; L - english / inglês; Northern PEA; authority / autoridade; decentralization / descentralização; governance / governação

Outcome Mapping: Building Learning and Reflection into Development Programs - Earl, Sarah; Carden, Fred; Smutylo, Terry (IDRC, 2001)
More and more, development organizations are under pressure to demonstrate that their programs result in significant and lasting changes in the well-being of their intended beneficiaries. However, such "impacts" are often the product of a confluence of events for which no single agency or group of agencies can realistically claim full credit. As a result, assessing development impacts is problematic, yet many organizations continue to struggle to measure results far beyond the reach of their programs. Outcome Mapping recognizes that development is essentially about people relating to each other and their environment. The originality of this approach lies in its shift away from assessing the products of a program to focus on changes in behaviour, relationships, actions, and activities in the people, groups, and organizations it works with directly. In doing so, Outcome Mapping debunks many of the myths about measuring impact. It will help a program be specific about the actors it targets, the changes it expects to see, and the strategies it employs and, as a result, be more effective in terms of the results it achieves. This publication explains the various steps in the outcome mapping approach and provides detailed information on workshop design and facilitation. It includes numerous worksheets and examples.
Keywords: *tagged; L - english / inglês; M - evaluation / avaliação; M - methodology / metodologia